Effects of a Flavonoid-Rich Fraction on the Acquisition and Extinction of Fear Memory: Pharmacological and Molecular Approaches - de Oliveira, Daniela R.; Zamberlam, Claudia R.; Rêgo, Gizelda M.; Cavalheiro, Alberto; Cerutti, Janete M.; Cerutti, Suzete M. (Frontiers in Behavioral Neuroscience, 2016)
The effects of flavonoids have been correlated with their ability to modulate the glutamatergic, serotoninergic and GABAergic neurotransmission; the major targets of these substances are N-methyl-D-aspartic acid receptor (NMDARs), serotonin type1A receptor (5-HT1ARs) and the gamma-aminobutyric acid type A receptors (GABAARs). Several studies showed that these receptors are involved in the acquisition and extinction of fear memory. This study assessed the effects of treatment prior to conditioning with a flavonoid-rich fraction from the stem bark of Erythrina falcata (FfB) on the acquisition and extinction of the conditioned suppression following pharmacological manipulations and on gene expression in the dorsal hippocampus (DH). Adult male Wistar rats were treated before conditioned fear with FfB, vehicle, an agonist or antagonist of the 5-HT1AR, GABAARs or the GluN2B-NMDAR or one of these antagonists before FfB treatment. The effects of these treatments on fear memory retrieval, extinction training and extinction retrieval were evaluated at 48, 72 and 98 h after conditioning, respectively. We found that activation of GABAARs and inactivation of GluN2B-NMDARs play important roles in the acquisition of lick response suppression. FfB reversed the effect of blocking GluN2B-NMDARs on the conditioned fear and induced the spontaneous recovery. Blocking the 5-HT1AR and the GluN2B-NMDAR before FfB treatment seemed to be associated with weakening of the spontaneous recovery. Expression of analysis of DH samples via qPCR showed that FfB treatment resulted in the overexpression of Htr1a, Grin2a, Gabra5 and Erk2 after the retention test and of Htr1a and Erk2 after the extinction retention test. Moreover, blocking the 5-HT1ARs and the GluN2B-NMDARs before FfB treatment resulted in reduced Htr1a and Grin2b expression after the retention test, but played a distinct role in Grin2a and Erk2 expression, according session evaluated. We show for the first time that the serotoninergic and glutamatergic receptors are important targets for the effect of FfB on the conditioned fear and spontaneous recovery, in which the ERK signaling pathway appears to be modulated. Further, these results provide important information regarding the role of the DH in conditioned suppression. Taken together, our data suggest that FfB represents a potential therapy for preventing or treating memory